Evaluating the Effectiveness of Cassava Wastewater Treatment in a Low Cost Microbial Fuel Cell - , R. A. Olaoye; , O. D. Afolayan; , T. A. Idowu; , S. A. Olayinka (Archives of Current Research International, 2018)
The performance of two-chambered low-cost microbial fuel cell (MFC) with cassava wastewater was evaluated for the effective treatment of polluting content. Two 30 L plastic containers were used to serve as anode and cathode chamber. The electrodes were made from readily available carbon papers sew together with naked copper wire while the salt bridge was made of inverted ‘U’ shaped PVC pipes. Results revealed that the removal efficiency for magnesium and cyanide were low while the 5-day biochemical oxygen demand (BOD5) and chemical oxygen demand (COD) removal were 65% and 53%, respectively. Increase in the voltage and power was observed at the beginning of the degradation which later gradually decreased with time. The maximum current generation (0.76 mA) was observed at an external load of 1000 Ω with a maximum voltage of 0.75 V while power obtained was 5.63x10-4 Watt. The coefficient of determination (R2) obtained was 0.9875, 0.9878 and 0.9926, for voltage, current and power, respectively. Plots indicated a best fitted model with the obtained data. It was revealed from the study that MFC can provide a sustainable and cheap means of treating cassava wastewater in developing countries with dual advantage of power production. The treatment technique would reduce environmental pollution from the usual indiscriminate disposal on land and water.